Assessing the Impact of Academic Self-Efficacy on Academic Performance of University Science Students in Katsina State, Nigeria - Isah, Suleiman A.; Olutola, Adekunle Thomas; Olatoye, Rafiu Ademola; Aderogba, Adegoke Adediji (Indonesian Journal of Teaching in Science, 2021)
This study assesses the impact of academic self-efficacy on the academic performance of university science students in Katsina State, Nigeria. One research question and three null hypotheses were formulated. A descriptive survey research design was adopted where 320 randomly selected students from mathematics, physics, chemistry, and biology departments in the four universities in the state were selected. Academic Self-Efficacy Scale and students CGPA record was used as data collection tools which were analyzed using frequency count, percentage, Pearson Product Moment Correlation, Linear Regression, and ANOVA. The result of the study revealed that the majority of the students have either moderate or high academic self-efficacy, but belong to either a third class and/or lower second class degrees. A weak significant positive correlation existed between students’ academic self-efficacy and performance (r = 0.12; p0.05). Self-efficacy significantly contributed 1.5% to the total variance of academic performance (R2 = 0.015, F1, 292 = 4.03; p0.05). However, there is no significant difference in the academic performance of low, moderate, and high academic self-efficacious students (F2, 292 = 2.318, p0.05). The researchers recommend that school counselors should improve students’ academic self-efficacy to enhance students’ academic performance.